Uma análise econométrica do Programa um Computador por Aluno - Alex Felipe Rodrigues Lima; Adolfo Sachsida; Alexandre Ywata de Carvalho (Instituto de Pesquisa Econômica Aplicada (IPEA), 2018)
– The purpose of this study is to evaluate the impact of the One Computer Per Student Program (Prouca), from the National Education Development Fund (FNDE), performance in the Brazil Test (Prova Brasil) and the National High School Examination (ENEM), both at school level, using the differences-in-differences method combined with the propensity score matching (PSM), and at the student level, using the PSM. The results showed that the program had a positive impact on students' performance in the final years of the Brazil Test (Portuguese and mathematics) and in the Enem language and codes and writing tests in 2010, as well as in all tests in 2011 - including the average of the exams - except in writing. At the school level, the program had a positive impact on the writing test and the average of the Enem assessments, the analysis between 2009 and 2010, and the natural science and writing tests as well as in the total average, in the research between 2009 and 2011.
Keywords: C32; D04; 330; One Computer Per Student Program; Enem; Brazil Test; differences in differences; propensity score matching